Implications of ESC-high tthrombotic risk features and ARC-high bleeding risk criteria on clinical outcomes in all-comer patients undergoing PCI. (14th October 2021) - Wang, H Y; Dou, K F; Mo, R A N; Guan, C D; Yin, D; Xu, B
Abstract: Background: High thrombotic risk (HTR) and high bleeding risk (HBR) features after PCI can occur in the same patient. The individualized risks of ischemic vs. bleeding events are needed to be considered for determining the optimal duration of DAPT. We aimed to evaluate long-term ischemic and bleeding outcomes in patients who are at both HTR and HBR after DES implantation. Methods: All consecutive patients who underwent PCI with DES were prospectively enrolled in Fuwai PCI Registry. HTR criteria based on 2017 ESC DAPT guidelines were defined as: diffuse multivessel diabetic CAD patients, chronic kidney disease, ≥3 stents implanted, ≥3 stents lesions treated, bifurcation with two stents implanted, total stent length >60 mm, or chronic total occlusion. Patients were defined as HBR if they met at least 1 major or 2 minor Academic Research Consortium (ARC)-HBR criteria. The primary ischemic outcome was major adverse cardiac event (MACE), a composite of cardiac death, myocardial infarction, target vessel revascularization and stent thrombosis. Results: Among 10, 167 patients, 4, 430 (43.6%) qualified as HTR. The rate of HBR patients was significantly higher in the HTR group than in the non-HTR group (18.9% versus 12.2%, P<0.001). Compared to those having non-HTR., Patients with ESC-HTR had higher 30-month rates of MACE (hazard ratio [HR] adjust: 1.56, 95% confidence interval [CI]: 1.34–1.82; P<0.001), device-oriented composite endpoint (composite of cardiac death, target-vessel MI, and target lesion revascularization) (HRadjust: 1.52 [1.27–1.83]; P<0.001), cardiac mortality, myocardial infarction, stent thrombosis, any revascularization, and stroke, without increasing the risk of BARC type 2, 3, or 5 bleeding. MACE rates at 30 months among those without HTR or HBR, HBR alone, HTR alone, and both HTR and HBR were 5.1%, 6.0%, 8.3%, and 8.8%, respectively (P<0.001). Associations between HTR and adverse events were similar in HBR and no HBR groups, without evidence of interaction; however, adverse event rates were highest among subjects with both HBR and HTR. Conclusions: A combination of ESC-HTR and ARC-HBR may increase the risk of long-term ischemic events, including cardiac mortality, emphasizing the importance of considering the net clinical benefit including high ischemic and bleeding features. Our data suggest that ESC-HTR criteria was useful for stratifying post-PCI patients into risk strata for future ischemic events. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Beijing Municipal Health Commission (Grant No. 2020-1-4032)